Nutrition, Choice and Health-Related Claims - De Magistris, Tiziana (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book presents different articles focused on the role of nutritional properties and/or health-related claims on choice preferences, choice behavior, healthy eating/healthy diet, and the willingness to pay for certain foods.
English
Keywords: allergen; n/a; consumer home-test; cereal grains; non-communicable diseases; health information; trans-fatty acids; health halo; Aragón; nutritional knowledge; WTP; Food Neophobia Scale (FNS); qualitative; choice architecture; plant extract; organic consumer choices; loglinear analysis; exposure time; purchase intentions; food labelling; functional ingredients; greenhouse gas emissions; non-communicable disease; functional food; food labels; dietary fiber; dining environment; food choices; changes in quality; random forest; local; labeling; segmentation; cluster analysis; nudging; policy; green tea; United Kingdom; health; menu; perceptions; nutritional labels; consumer research; vitamins; quantile regression; nutritional claims; information; market success; red wine; qualified health claim; alcohol content; cross-cultural comparison; health attitudes; environmental information; health consciousness; nutrition claims; health claim; choice experiment; organic dried strawberries; emotional eating